β2* nAChRs on VTA dopamine and GABA neurons separately mediate nicotine aversion and reward - Grieder, Taryn E. (Proc Natl Acad Sci U S A, 2019)
Evidence shows that the neurotransmitter dopamine mediates the rewarding effects of nicotine and other drugs of abuse, while nondopaminergic neural substrates mediate the negative motivational effects. β2* nicotinic acetylcholine receptors (nAChR) are necessary and sufficient for the experience of both nicotine reward and aversion in an intra-VTA (ventral tegmental area) self-administration paradigm. We selectively reexpressed β2* nAChRs in VTA dopamine or VTA γ-amino-butyric acid (GABA) neurons in β2(−/−) mice to double-dissociate the aversive and rewarding conditioned responses to nicotine in nondependent mice, revealing that β2* nAChRs on VTA dopamine neurons mediate nicotine’s conditioned aversive effects, while β2* nAChRs on VTA GABA neurons mediate the conditioned rewarding effects in place-conditioning paradigms. These results stand in contrast to a purely dopaminergic reward theory, leading to a better understanding of the neurobiology of nicotine motivation and possibly to improved therapeutic treatments for smoking cessation.